Influence of Ultra-high Strength Concrete on Circular Concrete-filled Dual Steel Columns. (February 2017) - Romero, Manuel L.; Ibañez, C.; Espinos, A.; Portolés, J.M.; Hospitaler, A.
Abstract: This paper presents the results of an experimental program where the load-bearing capacity at room temperature of 14 slender circular concrete-filled dual steel tubular (CFDST) columns under axial load was analysed. In this study, two specimens were prepared as ordinary concrete-filled steel tubular (CFST) columns to be used as references to evaluate the mechanical contribution of the inner steel tube and its infill in the CFDST columns. In addition, the effect of two types of concrete: normal strength concrete (NSC) and ultra-high strength concrete (UHSC) was assessed. Besides, in order to study the influence of the steel share between the inner and outer tube, different cross-sectional configurations were considered. Since the number of experimental results available in the literature on slender CFDST columns is scarce, this work provides novel results to this research field. The different influence of the steel distribution in the response of the specimens of each series was observed, with no influence in the case of columns with ultra-high strength concrete in the outer ring. Finally, the current provisions of Eurocode 4 for the design of composite columns were assessed by means of the results of these tests, being necessary more test data to extract solid conclusions about their accuracy and reliability.